1993
DOI: 10.1080/07315724.1993.10718362
|View full text |Cite
|
Sign up to set email alerts
|

Plasma glucose and insulin responses to bananas of varying ripeness in persons with noninsulin-dependent diabetes mellitus.

Abstract: With progressive ripeness there is a decrease in starch and an increase in free sugar content of bananas. The starch also is considered to be poorly digestible. Therefore, we decided to study plasma glucose, serum insulin, C-peptide, and plasma glucagon responses to bananas with increasing degrees of ripeness. Seven male subjects with untreated noninsulin-dependent diabetes mellitus ingested 50 g carbohydrate as bananas of stage 4 (more yellow than green), 5 (yellow with green tip), 6 (all yellow), and 7 (yell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The effect of ripeness or maturity on the digestion and absorption of carbohydrate in fruits had been shown by studies of Wolever et al , 7 Hermansen et al , 8 Ercan et al , 9 and Lintas et al 10 Using bananas, their studies on ripeness had shown that digestibility increased as the fruits ripened, since their starch content decreased dramatically and was converted into free sugars. The actual sugar composition of fruits may not only be affected by maturity but also by cultivar, the soil, climatic conditions, time of harvest, the length and method of storage.…”
Section: Resultsmentioning
confidence: 97%
“…The effect of ripeness or maturity on the digestion and absorption of carbohydrate in fruits had been shown by studies of Wolever et al , 7 Hermansen et al , 8 Ercan et al , 9 and Lintas et al 10 Using bananas, their studies on ripeness had shown that digestibility increased as the fruits ripened, since their starch content decreased dramatically and was converted into free sugars. The actual sugar composition of fruits may not only be affected by maturity but also by cultivar, the soil, climatic conditions, time of harvest, the length and method of storage.…”
Section: Resultsmentioning
confidence: 97%
“…Wolever et al [28] found a higher glycaemic response to ripe banana compared to unripe ones. However, a study by Ercan et al, [29] found little variation in the glycaemic response to varying degree of ripeness of banana.…”
Section: Discussionmentioning
confidence: 95%
“…[12] found that ripe banana produced a higher glycemic response than unripe banana; Ercan et al. [13] however, found little variations in glucose responses to bananas of varying ripeness thus suggesting that other factors may be contributory to the differences in glucose responses to fruits. There was no reliable method of ensuring the same degree of ripeness of all the fruits consumed in our study.…”
Section: Discussionmentioning
confidence: 99%